THE BLACK SEA GRAIN INITIATIVE SEBAGAI UPAYA BINA DAMAI KONFLIK RUSIA UKRAINA - Nisa, Dinda Fadlatun; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research analyzes the role of the Black Sea Grain Initiative as a peacebuilding effort in the Russia Ukraine conflict. The Black Sea Grain Initiative On February 24, 2022, the armed conflict between the Russian Federation and the Ukraine between the Russian Federation and Ukraine was escalating. This would disrupt wheat production and exports and accelerate price increases in developing countries that depend on imports imports as Russia and Ukraine are major wheat exporters. To allow the export of grain and other foodstuffs from Ukraine through the secure maritime corridors from Ukraine's three main ports, Chornomorsk, Odesa, and Yuzhny/Pivdennyi on the Black Sea to the rest of the world, the Russian Federation, Turkey, Ukraine, and the UN announced this initiative on July 22, 2022. The initiative in Istanbul established the Joint Coordination Center (JCC), which consists of senior representatives from the Russian Federation, Turkey, Ukraine and the UN. This research uses a qualitative method, with data collection techniques through literature studies and document analysis from several books, journals, articles, websites. This research uses the perspective of Pluralism and the theory of Peace Building The results of the paper indicate that the Black Sea Grain Initiative was created to regulate food supply to reduce the impact of conflict. With the entry of Ukrainian grain into the international market and Russia's recent decision to extend the deal for 60 days, it is important to investigate the impact of this initiative on world food security. Amidst the debate, it is also important to recognize the advantages of cooperation in addressing unusual security challenges. Keywords: The Black Sea Grain Initiative, Peace Building, Food Security, Global Markets.